Disease state changes and safety of long‐term donepezil hydrochloride administration in patients with Alzheimer's disease: Japan‐Great Outcome of Long‐term trial with Donepezil (J‐GOLD). Issue 5 (11th July 2018) - Arai, Heii; Hashimoto, Naoyuki; Sumitomo, Kenta; Takase, Takao; Ishii, Mika
Abstract : Background: A long‐term, large‐scale study of donepezil hydrochloride in patients with Alzheimer's disease (AD) was conducted. Previously, two interim reports were published during this study. We have now completed the study and herein present our analysis of the final results. Methods: The subjects of this study included AD patients who received the drug for the first time (newly treated patients), as well as AD patients who were already receiving the drug at the start of the study (continuously treated patients). The observation period was 48 months. Changes in cognitive function and severity of dementia associated with the drug administration and its safety were assessed. Results: Cognitive function decreased significantly after 24 months in newly treated patients and after 6 months in continuously treated patients, compared with baseline. The percentages of patients whose dementia severity improved or remained the same compared with baseline were 59.27% at 48 months in the newly treated patients and 57.09% at 48 months in the continuously treated patients. There were no major safety problems with the drug. Conclusions: We conducted a large‐scale study of AD patients in Japan. Here, we present our analysis of the final results and describe current clinical practice with the drug, changes in cognitive function and dementia severity associated with long‐term administration of the drug, and the drug's safety.